Effect of Dosage and Time Interval of Application of Liquid Organic Fertilizer Gamal Leaves on Growth and Yield of Mustard Plants (Brassica Juncea L.) - Andreas Budi Santoso (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
The purpose of this study was to determine the effect of the dose and time interval of applying organic Gamal leaf fertilizer on the growth and yield of mustard (Brassica junceaL). The study was conducted from March 2019 to May 2019 at the STIPER East Kutai Agrotechnology Experimental Garden. The design used was a Completely Randomized Design (CRD), with a factorial pattern, where the treatment of giving a dose of organic Gamal leaf fertilizer consisted of 4 treatments, namely: D0 = 0 ml L- 1, D1 = 40 ml L-1, D2 = 80 ml L-1, D3 = 120 ml L-1, while the time interval treatment consisted of 3 treatments, namely I1 = once every 3 days, I2 = once every 5 days, I3 = 7 days once. All treatments were repeated 3 times. Data were analyzed by analysis of variance followed by the smallest significant difference test at a significance level of 5%. The variables observed included the height of the mustard plant, the number of leaves of the mustard plant, the fresh weight per plant of the mustard greens. There was no interaction between the dosage of liquid organic fertilizer of Gamal leaves and the time interval of administration of all the variables measured. significantly to plant height (8.332), number of leaves (7.911) and fresh weight (7.027), while the time interval treatment had a significant effect only on plant height (8.076) and number of leaves (7.683).